Regenerative Chatter Evaluation when Turning Nickel-based Superalloy GH4169 Using PCBN Cutting Tool - Fadul Almula, Mubarak A.M.; Zhu, Haitao; Wahab, Hassan A. (Journal of Engineering and Technological Sciences, 2019)
Vibration during machining operation is a major issue that lowers cutting operation efficiency. Usually high cutting forces are encountered during machining processes, consequently shortening cutting tool lifetime. Thus, the metal removable rate is reduced and a poor surface finish is produced. This issue can be overcome by selecting proper cutting parameters (cutting speed, feed, and depth of cut), especially when machining difficult-to-cut materials at high cutting speed. In this paper, a two-degrees-of-freedom turning vibration model is introduced to study the vibration mode of the system when nickel-based superalloy GH4169 is turned at varying cutting depths. The effect of varying the cutting depth on system vibration was simulated using the Matlab/Simulink software. In addition, the model was experimentally tested on a numerical controlled lathe machine. The stable limit cutting depth and the main vibration directions of the system chatter were the responses that were investigated. The results show that the simulation provided a reasonable approximation of the experimental results.